2018
DOI: 10.12681/jhvms.15567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of tramadol on analgesic response and locomotor activity on two different strains of laboratory mice

Abstract: Analgesia of laboratory animals consists an important component in experimental studies where painful stimuli or procedures may take place. When choosing analgesics, the severity of pain along with the response to medication is among the factors that determine the choice of agent. Tramadol is a known synthetic opioid analgesic used to treat main acute or chronic pain including perioperative pain. The purpose of this study was to evaluate the analgesic response as well as the effect on locomotor activity in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…According some previous similar results TRA abuses especially in high doses in has harmful role of motor activity and also induces anxiety and depression while in low mentioned doses this effects was not signi cant [17,29]. Previous studies have indicated that TRA can act as a motor activity modulator which its effects depends on its doses [30][31][32]. In spites of all data about role of TRA on neurobehavioral changes but its clear mechanism and involved molecular and signaling pathways in these mood and motor activity related behavioral changes wan not de ned and clari ed yet [3,33,34].…”
Section: Discussionmentioning
confidence: 94%
“…According some previous similar results TRA abuses especially in high doses in has harmful role of motor activity and also induces anxiety and depression while in low mentioned doses this effects was not signi cant [17,29]. Previous studies have indicated that TRA can act as a motor activity modulator which its effects depends on its doses [30][31][32]. In spites of all data about role of TRA on neurobehavioral changes but its clear mechanism and involved molecular and signaling pathways in these mood and motor activity related behavioral changes wan not de ned and clari ed yet [3,33,34].…”
Section: Discussionmentioning
confidence: 94%